Policing in India: Need of Effective Preventive Actions to Tackle Crime and Criminality - Pradeep Kumar Singh (Jurnal Media Hukum, 2021)
When the criminal justice system is seen on the face, it may appear that actions are initiated only after the commission of a crime. Accordingly, criminal law can prescribe punishments for already committed criminal acts. However, a detailed and proper analysis of criminal justice clarifies that its main objective is the prevention of crime and criminality. Prevention of crime is taking action at the incipient stage means before the commission of a crime. The criminal justice system always provides crucial spaces for preventive actions. Proper and efficient police actions ensure effective tackling of crime and criminality, particularly police actions at the incipient stage. In India, in the 21st-century, crime and criminality are creating a serious challenge where the nature of crime is becoming more serious, and the crime rate is increasing. In such a situation, analysis of the Indian criminal law is vital to find out whether it sufficiently empowers Indian police for preventive actions to tackle crime and criminality. Analysis of Indian Criminal Law shows that provisions for directing and enabling policing are already provided. Despite that, training is necessary for the police officers to use the modern know-how for resorting to preventive actions.